A Cloud Adoption Feasibility Assessment Framework (CAFAF) for E-Government in Developing Countries: A Design Science Approach - Pokhrel, Bikash (Auckland University of Technology, 2022)
The purpose of the study was to determine whether cloud computing could be beneficial in improving the success of E-Government implementation in developing countries such as the Federal Democratic Republic of Nepal. Cloud computing has often been reported in the literature as effective and efficient in managing IT resources at a national level. Developed countries have paid substantial attention to embracing technological innovations through cloud computing and catering to the potential for E-Government applications in the form of Government Private Cloud, also referred to as G-Cloud. In contrast, developing countries have been unable to take full advantage of the Government Private Cloud models adopted by developed countries due to underlying challenges, such as poor ICT infrastructure, skills shortages, and a lack of financial and internal resources. The literature on theoretical cloud concepts has overlooked the technological and economic feasibility needs of cloud computing in a practical E-Government context and considering the role of stakeholder involvement. Cloud vendor tools offered limited approaches to the cloud feasibility assessment - particularly those at an agency or department level. These vendor tools often ignored considerations of government agency-specific needs or their political context. Due to government agencies' varying business, political and technological needs in developing economies, cloud adoption feasibility differs from agency to agency. Despite the interest shown by several studies, no authors, to date, empirically studied the formulation of cloud adoption feasibility assessment tools based on a conceptual cloud computing framework. Therefore, this study was conceived to identify important factors influencing cloud adoption in developing countries through a literature review and then to develop a new framework that may be useful for E-Government cloud consideration. The study aimed to propose, evaluate, and refine a new Cloud Adoption Feasibility Assessment Framework (CAFAF) to assist agencies in deciding whether or not the cloud can be appropriate for implementation. The study followed the Design Science Research approach (guided by Johannesson and Perjons (2012) and Vaishnavi and Kuechler (2004). The Design Science Research (DSR) paradigm aligned well with the research motivation and objectives and ultimately provided an excellent research process for the resulting outcome in the framework. Four DSR design phases were used to improve the CAFAF and associated automated calculation spreadsheet tools, resulting in six artifacts, each composed of several constructs and sub-constructs. The core contribution of this study has been the creation of a new decision-making CAFAF framework and the associated calculation spreadsheet tools for a cloud feasibility assessment relevant to developing countries. Highly valuable are the spreadsheets that are directly accessible for decision-makers in government and others navigating feasibility planning for cloud migration and business case development. The CAFAF and its associated tools represent a significant new contribution to the design of service-oriented frameworks that can assist in E-Government agency decision-making. The findings identified that common industry cloud feasibility and migration frameworks needed to improve to take into consideration a more holistic view and to develop supporting tools that can investigate the relevance of cloud computing with stakeholders’ varying needs and their context in mind. This study addresses a gap in the absence of a vendor-independent feasibility assessment tool tailored to the context of developing countries and contributes to the emerging cloud computing research domain where the focus in the context of a developing country's government agencies has been found to be substantially scant in publications compared to those in developed economies.